Use of Ai-Powered Tutoring Systems for Personalized English Language Learning Among Colleges of Education Students in Lagos State, Nigeria - James Adekunle Adedokun; Adeyinka Ayoola Olabode (Proceeding of the International Conference on Global Education and Learning, 2024)
This study evaluates the effectiveness of AI-powered tutoring systems in enhancing personalized English language learning among students in Colleges of Education in Lagos State, Nigeria. The primary objectives include assessing the impact of these systems on students' English proficiency and evaluating their perceptions of usability and effectiveness. Guided by four research questions, the study aims to provide insights into the integration of AI in educational contexts. Employing a survey research design, the study targeted a population of approximately 50,000 final-year students across several Colleges of Education. A sample of 400 students was selected using a combination of convenience and stratified random sampling techniques, ensuring representation from two institutions: the Federal College of Education (Technical) Akoka (FCET) and the Adeniran Ogunsanya College of Education (AOCOED). A structured questionnaire with 30 items was developed and validated, achieving a reliability coefficient of 0.81. Data collection methods included both in-person and online approaches, yielding a response rate of 74.5% (298 completed questionnaires). Data were analyzed using descriptive statistics and t-test for hypothesis testing. The findings revealed a significant difference in English language proficiency between students using AI tutoring systems and those using traditional methods, with the AI group reporting better outcomes. Additionally, students expressed mixed perceptions regarding the usability of AI systems. Major recommendations include enhancing AI system functionalities, providing comprehensive training for users, and addressing technological barriers to ensure effective implementation. This study underscores the potential of AI in education while highlighting the need for ongoing improvements and support mechanisms.